Beneficial Property Taxation for Emerging Market Countries Addressing Climate Change and Post-Pandemic Recovery - Ahmad, Ehtisham; Brosio, Giorgio (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book presents a new approach to recurrent property taxation based on occupancy, size, and location, that will strengthen local governments. Reflecting on the concept of "beneficial property taxation" first proposed by Alfred Marshall, the political economy constraints faced by traditional property taxation are examined and compared with evidence for beneficial property tax seen in China, Mexico, and sub-Saharan Africa. The benefits of this form of taxation are highlighted in relation to the financing of local public services and infrastructure that are required for sustainable development. This book provides a policy-oriented look at property taxation that engages with the sustainable development goals and lay the foundations for a post-pandemic recovery. It will be relevant to researchers and policymakers interested in development economics and the governance of taxation. Ehtisham Ahmad has been Visiting Professor at the LSE Grantham Research Institute, Pao Yu-Kong Professor at Zhejiang University and has held senior positions at the IMF. Giorgio Brosio is Emeritus Professor of Economics at the University of Torino.
1. Property Taxation, Instruments, Models, Administration, and Potential Effects -- 2. Failure and Promise of Property Taxation in Senegal -- 3. Challenges of Property Taxation in Tanzania -- 4. Financing Sustainable Local Spending and Infrastructure in China -- 5. Mexico: Failure of the Traditional Property Tax and Proposed Beneficial Property Tax Alternative -- 6. Administration of Property Taxes -- 7. Toward a Beneficial Property Tax Agenda for Sustainable Growth.
Keywords: Development economics; Power resources; Environmental economics; Economics; Social choice; Finance; Development Economics; Resource and Environmental Economics; Public Choice and Political Economy; Financial Economics